2019
DOI: 10.1002/ejic.201900483
|View full text |Cite
|
Sign up to set email alerts
|

Cages vs. Prisms: Controlling the Formation of Metallosupramolecular Architectures with Ligand Side‐Chains

Abstract: Metallosupramolecular assemblies of the general formula M2nLn can adopt prismatic or cage‐like structures. The factors controlling the aggregation number n and the geometry of the final assembly are still not fully understood. Here, we describe the synthesis and the structural characterization of PtII8L4 complexes, which adopt tetragonal prismatic structures. The bridging ligand L features four pyridyl groups and an inert FeII clathrochelate complex at its core. Furthermore, the ligand has three phenanthrene g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…As can be seen from Table 2 and Table 3 , the φ values for n -butylboron- and adamantylboron-capped iron(II) tris-octoximates [ 5 , 36 ] are higher than those for their tris-nioximate analogs, while other geometrical parameters of their macrobicyclic frameworks are very similar. In particular, the averaged Fe–N distances in all these molecules are close to 1.90 Å, thus they are characteristic of the macrobicyclic iron(II) tris-α-dioximates [ 1 , 2 ], and their oligo- and polymeric derivatives [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] as well, which are reported to be the diamagnetic compounds. Indeed, Fe–N distances in the high-spin iron(II) complexes, the derivatives of N -donor ligands, are typically higher than 2.0 Å [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from Table 2 and Table 3 , the φ values for n -butylboron- and adamantylboron-capped iron(II) tris-octoximates [ 5 , 36 ] are higher than those for their tris-nioximate analogs, while other geometrical parameters of their macrobicyclic frameworks are very similar. In particular, the averaged Fe–N distances in all these molecules are close to 1.90 Å, thus they are characteristic of the macrobicyclic iron(II) tris-α-dioximates [ 1 , 2 ], and their oligo- and polymeric derivatives [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] as well, which are reported to be the diamagnetic compounds. Indeed, Fe–N distances in the high-spin iron(II) complexes, the derivatives of N -donor ligands, are typically higher than 2.0 Å [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, we have investigated Co clathrochelate complexes with phenanthrenequinone dioximato ligands, which are potentially redox non-innocent. [13] The Co(II) complex 5 was prepared in 37 % yield from CoCl 2 , phenanthrenequinone dioxime, [14,15] and phenylboronic acid. Complex 5 shows good solubility in CH 2 Cl and HF.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of elongated tetratopic pyridyl-based ligands and cis -protected square-planar metal centers has been shown to yield a variety of trigonal, tetragonal, pentagonal, and hexagonal barrel-like structures ( 224 – 227 ; Figure ). , Intriguingly, recent reports have demonstrated that ligands of this class can also form structures with gyrobifastigium, triangular-orthobicupola, , and square-orthobicupola geometries ( 228 – 230 ), in some cases selectively and in others as a minor product. Thus, while the combination of elongated tetrapyridyl ligands with cis -protected square-planar metal centers can yield different structures (Figure ), control over the thermodynamics of the system is required to ensure that a single product is formed.…”
Section: Geometric Steric and Subtle Non-covalent Effectsmentioning
confidence: 99%
“…Geometries that can be formed by the combination of elongated tetratopic N-donor ligands and cis -protected square-planar metal centers in a 1:2 ratio. Reproduced with permission from ref . Copyright 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Geometric Steric and Subtle Non-covalent Effectsmentioning
confidence: 99%